The Effectiveness of Humorous Stories to Teach English Speaking Skills - Putri, Mai Lany Sudarno; Fahri, Fahri (RETAIN : Journal of Research in English Language Teaching, 2023)
This study examined if humorous stories might help students in SMA Labschool at UNESA’s eleventh grade improve their speaking abilities. The goal of this study is to collect empirical data on the variations in speaking test scores between students who were taught using humorous stories. There were 90 students make up the overall population of this study, with the following breakdown: 21 students in class XI-IPA 1, 19 students in class XI-IPA 2, and 20 students in class XI-IPA 3, 30 pupils in IPS class XI. This study employed a pre-experimental research design. Through the use of pretest and posttest, the data was gathered. It aimed to determine if humorous stories bring any differences in students’ scores. According to test results, the students’ pre-test mean score was 60.80, but their post-test mean score was 75.70. According to table 4.5, the significance value (2-tailed) for this occurrence is 0.000 < 0.05. Therefore, Ha is approved whereas Ho is disapproved. In other words, using humorous stories has a significant influence on the speaking skills of 11th grade students of SMA Labschool UNESA.